2004
DOI: 10.1186/cc2828
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Of brain-injured patients admitted to intensive care units, a significant number acquires nosocomial infections. Increased susceptibility to infectious agents could, at least partly, be due to transient immunodepression triggered by brain damage. Immune deficiency in patients with severe brain injury primarily involves T cell dysfunction. However, humoral and phagocytic deficiencies are also detectable. Activation of the hypothalamo–pituitary–adrenal axis and the sympathetic nervous system plays a crucial role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 39 publications
1
27
0
1
Order By: Relevance
“…A number of predisposing factors are considered to account for the high incidence of bacterial pneumonia following stroke, including several factors known to facilitate aspiration, such as impaired protective reflexes, dysphagia and mechanical ventilation [4,6,25]. In addition, experimental and clinical evidence suggests that acute central nervous system injury, including stroke, directly impairs antibacterial host defence, thereby increasing susceptibility to infections [26,27,28,29]. In particular, down-regulation of systemic cellular immune responses, i.e.…”
Section: Immune and Stress Markers For The Prediction Of Post-stroke mentioning
confidence: 99%
“…A number of predisposing factors are considered to account for the high incidence of bacterial pneumonia following stroke, including several factors known to facilitate aspiration, such as impaired protective reflexes, dysphagia and mechanical ventilation [4,6,25]. In addition, experimental and clinical evidence suggests that acute central nervous system injury, including stroke, directly impairs antibacterial host defence, thereby increasing susceptibility to infections [26,27,28,29]. In particular, down-regulation of systemic cellular immune responses, i.e.…”
Section: Immune and Stress Markers For The Prediction Of Post-stroke mentioning
confidence: 99%
“…In a 2001 human study, severe immune suppression was observed following severe TBI. Eighteen to seventy-two hours after head trauma, the numbers of circulating T-cells, T-helper cells, T-suppressor [92,93] and NK cells were reduced while the B-lymphocyte count remained normal [92]. There was also an increase in CD4+/CD45+ T cells [10,93].…”
Section: Introductionmentioning
confidence: 99%
“…Eighteen to seventy-two hours after head trauma, the numbers of circulating T-cells, T-helper cells, T-suppressor [92,93] and NK cells were reduced while the B-lymphocyte count remained normal [92]. There was also an increase in CD4+/CD45+ T cells [10,93]. The immune regulatory functions within the CNS following TBI, for example, microglia and astrocyte activation lead to antigen presentation to T-cells that alters their cytokine response and this may contribute to TBI pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Although aspiration due to a decreased level of consciousness may explain the development of pneumonia among some patients, research also suggests that catecholamines released as a result of brain injury-induced sympathetic activation may modulate cells of the immune system and induce systemic immunosuppression [15-20]. While this immune suppression may protect the brain from further inflammatory damage, it may also increase susceptibility to infection among those with acquired brain injury [16,17,19]. …”
Section: Introductionmentioning
confidence: 99%